Marcadores discursivos do Talian no programa radiofônico Un Pochetin dela Itàlia em Caibi, Santa Catarina - Zortéa, Tamires Regina (2019)
The present research investigated the use of talian discursive markers (MDs) in the radio program Un Pochetin dela Itàlia, broadcast on sundays, by Radio Caibi 96.7 FM and by the Internet, in the municipality of Caibi, Santa Catarina. The program began in 2005 and seeks to bring the caibian community closer to italian culture, as well as helping to maintain the talian. Understood as an italian immigration language in Brazil, the talian is a coiné whose origin is the venetian dialect in contact with other varieties of the italian language - coming mainly from the northern region of Italy, which includes Lombardy, Trentino -Alto Ádige and Friuli-Venécia Júlia (FROSI; MIORANZA, 1983) -, and with the Portuguese language of Brazil. Although the program Un Pochetin dela Itàlia is transmitted in talian, it was verified the use of many words and expressions in portuguese by the announcer - among them, the MDs stand out. The sample consisted of two transmissions of the program Un Pochetin dela Itàlia, each of three hours of the month of January, 2018. To enable the analysis, both transmissions were fully transcribed in the talian language and, from this, were selected the occurrences in which the MDs appeared in the speaker's speech. Following, formal and semantic-pragmatic criteria were identified and the language in which the MDs were produced, if talian, italian and/or portuguese. The analysis was supported by Linguistic Functionalism (GIVÓN, 1995). As main results, it is worth noting that the speaker used 19 different forms of MDs in the program, totaling 874 occurrences during the transmissions. Thus, the markers were perceived as a way of giving follow-up and fluency to the discourse. In addition, even though it was a talian program, the speaker also used italian and portuguese language markers, especially the latter, with great recurrence. This is due, in turn, to the instantaneousness of the radio, that is, the rush required on the speaker made him use also portuguese MDs to which he had access at the moment, and an MD from the italian, being similar to the talian, which is the phenomenon called code-switching. Finally, we found that, because most MDs have a medial position in sentences, it is understood that they were mainly used as a link and continuity function, since the speaker moves from one subject to another quickly and, therefore, has to resort to items to link these contents without causing uncomfortable moments to the listener. In the radio medium, there is a fear on the part of the communicators that there are moments of silence, pauses or hesitations during the transmission, which is live, due to the possibility of these factors causing the listener to change stations, which often occurs on the radio. Thus, it was observed that the MDs, as opposed to being language vices, have an important role for Social Communication, since in any of the languages in which they were used, they assisted the speaker in his goal of communicating well.